Identification of Key Variables in the Existence of Prima Dana Mandiri Cooperatives Through the Application of the MICMAC Method - I Gusti Ayu Asri Pramesti; Gde Bagus Brahma Putra (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2020)
Cooperatives are the cornerstone of the national economy based on family principles. The development of cooperatives in Bali has good potential in the future. Prima Dana Mandiri Multipurpose Cooperative is one of the cooperatives in Badung Regency and is undergoing experience development. The results of the Focus Group Discussion were analyzed using the Matrix of Cross Impact Multiplications Applied to aClassification (MICMAC) Software. Several key variables play a role in the existence of Prima Dana Mandiri Multi-Business Cooperative